Computational and experimental investigation of TmAgTe2 and XYZ2 compounds, a new group of thermoelectric materials identified by first-principles high-throughput screening. Issue 40 (13th August 2015) - Zhu, Hong; Hautier, Geoffroy; Aydemir, Umut; Gibbs, Zachary M.; Li, Guodong; Bajaj, Saurabh; Pöhls, Jan-Hendrik; Broberg, Danny; Chen, Wei; Jain, Anubhav; White, Mary Anne; Asta, Mark; et al.
Abstract : Promising thermoelectric materials ( XYZ 2 ) with high band degeneracy and low thermal conductivity. Abstract : A new group of thermoelectric materials, trigonal and tetragonal XYZ 2 ( X, Y : rare earth or transition metals, Z : group VI elements), the prototype of which is TmAgTe2, is identified by means of high-throughput computational screening and experiment. Based on density functional theory calculations, this group of materials is predicted to attain high zT ( i.e. ∼1.8 for p-type trigonal TmAgTe2 at 600 K). Among approximately 500 chemical variants of XYZ 2 explored, many candidates with good stability and favorable electronic band structures (with high band degeneracy leading to high power factor) are presented. Trigonal TmAgTe2 has been synthesized and exhibits an extremely low measured thermal conductivity of 0.2–0.3 W m −1 K −1 for T > 600 K. The zT value achieved thus far for p-type trigonal TmAgTe2 is approximately 0.35, and is limited by a low hole concentration (∼10 17 cm −3 at room temperature). Defect calculations indicate that TmAg antisite defects are very likely to form and act as hole killers. Further defect engineering to reduce such X Y antisites is deemed important to optimize the zT value of the p-type TmAgTe2 .